HELICOBACTER - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2023)
Distinguishing Features: Gram-negative spiral gastric bacteria with flagella; oxidase-positive, urease-positive; microaerophilic, grows at 37˚C on Campy or Skirrow agar